MBT for Functional Testing of Embedded Systems - Khan, Mohammed Naim; Arya, Namita; Singh, Amit Prakash (International Journal of Computer Sciences and Engineering, 2025)
Embedded Systems require combination of Software Electrical and Mechanical Engineering. This leads to increased complexity of Embedded Systems with shorter production cycle. These evolutions pose new challenges to traditional embedded system testing approaches, because besides time constraints, embedded system products are expected to meet quality constraints prior to their deployment in field. The Cost and Time of Testing Embedded Systems consumes a considerable portion of entire development cycle. With Increased Complexity of Embedded Software it becomes imperative that our Functional Testing is effective at detecting issues in the system. With the above requirements we propose to use Model Based Testing (MBT) for the functional testing of Embedded Systems during the manufacturing process in the production line. The comprehensive and systematic approach of MBT facilitates automated testing with reduced test time and cost along with improved quality of the product.